Traditional Chinese Medicine nursing of a patient with hemorrhagic shock after surgery for arteriosclerosis obliterans of the lower limb (下肢动脉硬化闭塞症术后失血性休克1例的中医护理) - ZHANG Lijing (章丽景); FANG Lina (方立娜) (中西医结合护理)
This paper summarized the Traditional Chinese Medicine nursing of a patient with hemorrhagic shock after surgery for arteriosclerosis obliterans of the lower limb. Comprehensive nursing interventions such as illness condition monitoring, postoperative complications prevention and psychological care were carried out. Traditional Chinese Medicine nursing techniques including Chinese herbal medicine oral care, auricular acupoint pressing, acupoint massage, ear-tip bloodletting, Chinese herbal medicine fumigation therapy were provided to prevent postoperative complications and improve the rehabilitation of the patient. (本文总结1例下肢动脉硬化闭塞症术后失血性休克患者的中医护理经验。护理人员在病情观察、并发症预防、心理护理等常规护理基础上, 根据中医辨证, 采取中药口腔护理、耳穴埋豆、穴位按摩、耳尖刺络放血、中药熏蒸操作等中医护理技术, 有效预防并发症, 改善了患者症状, 促进患者早期康复。)